Microbial Behavior of Imine Compounds on Bacteria (American International Journal of Biology and Life Sciences, 2019)
In  our  past  studies , some  imine  compounds  were prepared  m investigated , spectral  characterization  , it  gave good  evidence  for formation these   compounds , but in this  studying  , these  imine  derivatives  were   screened  against  some types  of   bacteria  and  microbes.